2017
DOI: 10.2495/dne-v12-n3-281-302
|View full text |Cite
|
Sign up to set email alerts
|

The economic value of landscape aesthetics in Albufera natural park through the analytic multicriteria valuation method

Abstract: The effective definition of public intervention goals and resource allocation for natural resource management requires decision makers to understand the monetary values of the full range of goods and services provided by landscapes, in other words, their Total Economic Value (TEV). Aesthetic enjoyment (AE) can be considered as part of such TEV of landscapes. For the estimation of the economic value of AE in Albufera Natural Park (Valencia, Spain), this paper applies the Analytic Multicriteria Valuation Method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…The Analytic Multicriteria Valuation Method (AMUVAM) is an approach that can be successfully used to estimate TEV and its five components. Examples of its application include the study by Estruch-Guitart & Vallés-Planells [18] who estimated the economic value of landscape aesthetics in Albufera National Park (Valencia, Spain). AMUVAM is a combination of two established techniques namely the analytic hierarchy process (AHP) and discount cash flow (DCF).…”
Section: An Overview Of Amuvammentioning
confidence: 99%
See 2 more Smart Citations
“…The Analytic Multicriteria Valuation Method (AMUVAM) is an approach that can be successfully used to estimate TEV and its five components. Examples of its application include the study by Estruch-Guitart & Vallés-Planells [18] who estimated the economic value of landscape aesthetics in Albufera National Park (Valencia, Spain). AMUVAM is a combination of two established techniques namely the analytic hierarchy process (AHP) and discount cash flow (DCF).…”
Section: An Overview Of Amuvammentioning
confidence: 99%
“…In AMUVAM, the known value of some of the components of TEV may be applied to derive the values of the remaining components [18]. The method permits the assessment of the relative importance and the monetary values of all the components of TEV which include the direct use values (DUV), indirect use values (IUV), option/quasi-option values (OV), existence value (EV), and bequest values (BV) [25].…”
Section: An Overview Of Amuvammentioning
confidence: 99%
See 1 more Smart Citation
“…Today's problems are focused on maintaining activities without endangering the natural values of the park. The new paradigm is now fully consolidated, and society believes that this area has a high natural value as opposed to its urbanization, which the scientists studied [27].…”
Section: Changing Paradigm People For Environmental Valuesmentioning
confidence: 99%
“…As such, they are one of the aspects that managers consider when prioritizing the environmental initiatives with greatest impact on the aspects most valued by society [12]. Several authors have shown that the establishment of incentives or policies favoring certain practices have an impact on landscape esthetics [13,14] and conversely, the monetary valuation of esthetics as a component of the economic value of landscape should influence policy-making [12].The philosophical discussion on the esthetics of nature has been about their foundations on pure emotion, judgments of taste, reasoning or knowledge; the objective or subjective nature of the experience; the esthetic categories; and their relationship with art (see for a comprehensive review [15,16]). The earliest source of esthetic considerations related to nature date from Greek philosophers.…”
Section: Introductionmentioning
confidence: 99%